PENGEMBANGAN BAHAN AJAR PAI DENGAN MODEL PENDIDIKAN BERPARADIGMA PROFETIK - Anam, Choirul (Al Tadib : Jurnal Ilmu Pendidikan, 2017)
Abstract: The article discusses the development of teaching materials of PAI with prophetic paradigm of educational model approach. As known, the essence of Islamic teachings included: belief, Shari'ah and morals. Three cores of Islamic teachings are then translated in the form of Rukun Iman, Pillars of Islam and Morals. And of the three was born Sciences Tauhid, Fiqh Arts and Sciences Morals. The third group of religious knowledge is then fitted with a discussion of the fundamentals of Islam hkum, namely; al-Quran and al-Hadith, and coupled with the history of Islam (dates), so that the start sequence Tauhid Science / Faith, Science Fiqh / Shari'ah, the Quran and al-Hadith, Morals, and Date /Islam history. To that end, teaching materials PAI largely abstract philosophical difficult to establish a scientific approach, akliyah. However, in accordance with their specialization, teaching materials of PAI was mostly abstract philosophical difficult to establish a scientific approach, akliyah. Therefore, the ability and skills of educators to mengkongkritkan abstract material was very necessary, although it was not easy. Criteria for selection and development of teaching materials of PAI, at the lack of six criteria that the material Festive of PAI should be able to fill the state philosophy of Pancasila, prioritizes teaching fundamental and thorough, in accordance with the level of development and maturity of the child, adapted to the environment that they are meaningful to the lives of children daily - day. taught on the level and type of school / madrasah should be terminal. given to every educational institution should be a continuous, integrated and aligned. Prophet Muhammad is a true learner and professor of world civilization, he gave the example of holistic learning method, so the selection of teaching materials of PAI should and should refer to him as a model. Keywords: Subjects, Approach, Prophetic